Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Ngọc Linh Hoàng

ac giúp e giải bài này với ạ. e cảm ơn ac

Nguyễn Lê Phước Thịnh
7 tháng 7 2022 lúc 19:43

a: \(A=\left(\dfrac{a-1}{2\sqrt{a}}\right)^2\cdot\left(\dfrac{a-2\sqrt{a}+1-a-2\sqrt{a}-1}{a-1}\right)\)

\(=\dfrac{\left(a-1\right)^2}{a-1}\cdot\dfrac{-4\sqrt{a}}{4a}=\dfrac{-\left(a-1\right)}{\sqrt{a}}\)

b: Để \(A=\dfrac{\sqrt{6}}{\sqrt{6}+1}\) thì \(\dfrac{-\left(a-1\right)}{\sqrt{a}}=\dfrac{\sqrt{6}}{\sqrt{6}+1}\)

\(\Leftrightarrow-\left(a-1\right)\left(\sqrt{6}+1\right)=\sqrt{6a}\)

\(\Leftrightarrow-a\sqrt{6}-a+\sqrt{6}+1-\sqrt{6}\sqrt{a}=0\)

hay \(a\simeq0.706\)


Các câu hỏi tương tự
Lyu O
Xem chi tiết
Thái Hoà Nguyễn
Xem chi tiết
Lưu Ninh Ma Kết
Xem chi tiết
ha quang minh
Xem chi tiết
Mina
Xem chi tiết
nguyenthibichhang
Xem chi tiết
Sơn Sarah
Xem chi tiết
Gút Boy
Xem chi tiết
Đinh Lan Phương
Xem chi tiết
Dury
Xem chi tiết